2011
DOI: 10.4314/ejhd.v25i1.69850
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Moringa stenopetala on blood parameters and histopathology of liver and kidney in mice

Abstract: Background: Moringa stenopetala and related species are commonly used in folk medicine for various human diseases such as antimalarial, antihypertensive, antidiabetic and as antispasmodic. Objective: The aim of the study is to evaluate the effects of aqueous extract of M. stenopetala on blood parameters, and histopathology of liver and kidney in experimental mice. Methods: Fresh leaves of M. stenopetala were collected from Arbaminch area, Southwest Ethiopia, in November 2005. The leaves were dried and extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 25 publications
9
29
1
Order By: Relevance
“…Ghebreselassie et al (2011) reported that aqueous leaf extract of M. stenopetala is shown to increase body weight and reduce serum glucose and cholesterol levels in mice. Serum glucose and serum cholesterol levels decreased significantly after six weeks of treatment.…”
Section: Antimicrobial and Medicinal Valuesmentioning
confidence: 99%
“…Ghebreselassie et al (2011) reported that aqueous leaf extract of M. stenopetala is shown to increase body weight and reduce serum glucose and cholesterol levels in mice. Serum glucose and serum cholesterol levels decreased significantly after six weeks of treatment.…”
Section: Antimicrobial and Medicinal Valuesmentioning
confidence: 99%
“…M. stenopetala is a native tree in arid and semi-arid regions in the southern Rift Valley of Ethiopia [21]. It is also reported to occur in Djibouti, Uganda and Sudan [22]. It is known by different vernacular names such as “Shiferaw” (Amharic), “Halako” (Gamo & Wollayita) [23], “Shelchada” (Konso), and “Cabbage tree” (English) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The various parts of M. stenopetala are extensively employed in the Ethiopian and Kenyan traditional medicine for treating a range of illnesses such as, diabetes, hypertension, stomach pain, malaria, leishmaniasis, leprosy, epilepsy, diarrhoea, asthma, colds, as an anthelmintic, emetic and wound healing [3]. Some of the recent pharmacological studies that appear to validate the claimed medicinal uses of the plant, primarily the leaves, include antimicrobial [4,5], antihypertensive [6][7][8], and blood glucose lowering and other favourable blood biochemical parameters [1,2,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%